The Occurrence of Stunting in Indonesia in 2023 - Cahyaningsih, Oktaviani; Cahyati, Widya Hary (Universitas Negeri Semarang, 2025)
Background: The nutritional status of toddlers is a serious issue that the government is trying to address. Various efforts have been made to reduce toddler nutrition problems, one of which is providing PMT to toddlers with stunting. Objective: to analyze the relationship between low economic status, exclusive breastfeeding, age of the baby at birth < 37 weeks, incomplete immunization status, and Low Birth Weight (LBW) < 2500 grams with stunting based on secondary data. Method: The research method used is quantitative research oriented with inductive logic, data collection was conducted using secondary data sourced from the 2023 Indonesian Health Survey (SKI) from 38 provinces in Indonesia. Data analysis used Scatter Plot processed with SPSS. Results: There is a positive relationship between low economic status, exclusive breastfeeding, the age of the baby at birth being < 37 weeks, and incomplete immunization status, with stunting. Conclusion: Factors such as low economic status, exclusive breastfeeding, age of the baby at birth < 37 weeks, and incomplete immunization status are associated with the occurrence of stunting.